2018
DOI: 10.1016/j.rmcr.2018.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Multiple circular pleural metastases of renal cell carcinoma

Abstract: A 91-year-old woman was admitted with persistent pyrexia, anorexia and weight loss. A chest radiograph showed multiple circular masses of various sizes. Chest computed tomography revealed multiple pleural tumors without any lung lesion. The ultrasound-guided biopsy specimens demonstrated diffusely-proliferated tumor cells with clear or vacuolated cytoplasm, which were positive for CD10, PAX8, vimentin and CAM5.2, but were negative for mesothelial cell markers such as HBME-1 and thrombomodulin. These findings i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Pleural involvement is very uncommon. In a study conducted in Japan, pleural involvement was found in up to 12% of autopsied patients [ 18 , 19 ]. Pleural involvement in renal cell carcinoma can be explained by the flow of blood from renal veins into the bronchial and intercostal veins via Batson's plexus and through lymphatic spread [ 11 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pleural involvement is very uncommon. In a study conducted in Japan, pleural involvement was found in up to 12% of autopsied patients [ 18 , 19 ]. Pleural involvement in renal cell carcinoma can be explained by the flow of blood from renal veins into the bronchial and intercostal veins via Batson's plexus and through lymphatic spread [ 11 , 19 ].…”
Section: Discussionmentioning
confidence: 99%